PERAN MEDIA KARTU KATA BERGERAK (FLASH CARD) DALAM MENGEMBANGKAN KOSAKATA BAGI ANAK DISLEKSIA MELALUI SIMULASI ROLE PLAYING “PASAR”: STUDI KASUS DI KELAS INKLUSI SDN PRAMBON KABUPATEN MADIUN - Resti Wulandari; Jeffry Handhika; Dwi Rosita Sari (CV Edujavare Publishing, 2026)
Students with dyslexia in inclusive classes often face specific challenges in developing vocabulary, which is the foundation for reading and writing skills. This study aims to analyze the role of moving word cards (flash cards) in developing vocabulary for dyslexic students through a